2016
DOI: 10.1002/jcb.25657
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of the Migratory and Invasive Phenotype of Ras-Transfected Mammary Cells by Photodynamic Therapy Treatment

Abstract: Photodynamic therapy (PDT) is a non-thermal technique for inducing tumor damage following administration of a light-activated photosensitizing drug (PS). In a previous work we found that PDT induces cytoskeleton changes in HB4a-Ras cells (human mammary breast carcinoma HB4a cells transfected with the RAS oncogene). In the present work we have studied the migratory and invasive features and the expression of proteins related to these processes on HB4a-Ras cells after three successive cycles of PDT using differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Cell migration of cells surviving PTN-PDT was determined employing a wound-healing assay 28 . The LM2 cells were seeded in 6-multiwell plates and allowed to grow until confluency, and afterwards, they were treated with PTN-PDT as indicated above.…”
Section: Methodsmentioning
confidence: 99%
“…Cell migration of cells surviving PTN-PDT was determined employing a wound-healing assay 28 . The LM2 cells were seeded in 6-multiwell plates and allowed to grow until confluency, and afterwards, they were treated with PTN-PDT as indicated above.…”
Section: Methodsmentioning
confidence: 99%
“…Although the maximum concentration of VP in the previous study was 2.0 μg/mL (Calvo et al, 2017), there were two studies that applied 1.0 μg/mL (Akens et al, 2014;Glidden et al, 2012). Because the lowest but effective concentration of VP must be determined, we conducted experiments at 0.01, 0.1, and 1.0 μg/mL in this study.…”
Section: Laser Irradiation and Vp Treatmentmentioning
confidence: 98%
“…The VP dose concentration and laser irradiation conditions were determined with reference to previous literature (Akens et al, 2014;Calvo et al, 2017;Celli et al, 2011;Mae et al, 2020), as shown in Table 1.…”
Section: Laser Irradiation and Vp Treatmentmentioning
confidence: 99%
“…on microtubules and cell endosomal transport (181). Other recent publications found phenotype shifts in macrophages elicited by temoporfin nanoparticles (163) and in Ras‐transfected mammary cells, where a reduction of the migratory and invasive ability was observed for cells treated with PDT using different photosensitizers including temoporfin (162). Sphingolipids and their ceramide subgroup are building blocks of membranes, but also fulfil numerous other functions in the cell and have been shown to be involved in PDT (95,169).…”
Section: Pharmacology and Biochemistrymentioning
confidence: 98%